2015
DOI: 10.1159/000371899
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Subfoveal Choroidal Thickness in Pseudoexfoliation Syndrome Using Enhanced Depth Imaging Optical Coherence Tomography

Abstract: Background/Aim: Pseudoexfoliation (PSX) syndrome is associated with blood flow disturbances; however, its exact effect on choroidal blood flow and thickness remains to be elucidated. This study compared subfoveal choroidal thickness in normal eyes and in eyes with PSX using enhanced depth imaging optical coherence tomography (EDI-OCT). Methods: This prospective, cross-sectional study included 35 eyes of 35 patients (20 males, 15 females) with unilateral or bilateral PSX and 26 eyes of 26 healthy volunteers (13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
8
0
3
Order By: Relevance
“…In our study, we did not find any difference in macular choroidal thickness in the PXS group when compared with the control group after adjusting for age and axial length. In a recent study, Turan-Vural et al 30 compared the subfoveal choroidal thickness of 35 PXS eyes with 26 healthy controls and found a significant decrease in the choroidal thickness in PXS eyes. 30 However, they did not adjust their analysis for confounding variables, including age and axial length, which might be a reason for this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not find any difference in macular choroidal thickness in the PXS group when compared with the control group after adjusting for age and axial length. In a recent study, Turan-Vural et al 30 compared the subfoveal choroidal thickness of 35 PXS eyes with 26 healthy controls and found a significant decrease in the choroidal thickness in PXS eyes. 30 However, they did not adjust their analysis for confounding variables, including age and axial length, which might be a reason for this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde koroid kalınlık öl-çümünün farklı cihazlar ile yapıldığı birçok ça-lışma mevcuttur. 9,[16][17][18][20][21][22] Branchini ve ark., koroid kalınlık ölçümünün farklı cihazlar ile tekrarlanabilir olduğunu göstermişlerdir. 26 Göktaş ve ark., PEX sendromlu hastalarda kontrol grubuna göre koroid kalınlığında incelme saptamış, bunun azalmış oküler kan akımına ve artmış vasküler rezistansa bağlı olabileceğini savunmuşlardır.…”
Section: Gereç Ve Yöntemlerunclassified
“…19 Turan-Vural ve ark., PEX sendromlu bireylerde oküler perfüzyon basıncında azalma ve koroid kalınlığında incelme olduğunu göstermiş-lerdir. 17 Eroglu ve ark. ise PEX materyali saptanan ve klinik olarak etkilenmiş gözlerde, etkilenmemiş göz ve kontrol grubuna göre koroidde anlamlı incelme bulmuşlardır.…”
Section: Gereç Ve Yöntemlerunclassified
See 1 more Smart Citation
“…In 1994, Helbig et al demonstrated progressive degeneration of the iris vasculature on electron microscopy, progressing from the adventitia to the endothelium; they concurrently demonstrated relative hypoxia in the aqueous humor of pseudoexfoliation patients when compared to control (44). More recently, decreased subfoveal choroidal thickness has been demonstrated in pseudoexfoliation eyes, with the suggestion that this may be due to decreased choroidal perfusion related to carotid flow as well as impairment of the choroidal microcirculation (45, 46). Kocaturk et al has reported increased vascular resistance in the ophthalmic artery in pseudoexfoliation glaucoma patients, as identified using color Doppler imaging (47).…”
Section: Ocular Manifestationsmentioning
confidence: 99%